PENGARUH KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DIREKTORAT JENDERAL PERHUBUNGAN LAUT DISTRIK NAVIGASI KELAS I DUMAI - Yeri Hardiyanti; Syakdanur Nas; Ngadlan Ngadlan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to figure out and analyze how significant the influence of job satisfaction toward the performance of officers at the Directorate General of Sea Communication Navigation District Class 1 Dumai. The analysis method used was quantitative descriptive method by distributing questionnaire to 66 respondents. Based on the calculation using SPSS 20, it shows that t count (6,854) > t table (1,669). Therefore, it shows that there was significant influence between job satisfaction and performance of officers at the Directorate General of Sea Communication Navigation District Class 1 Dumai. Based on the result of determination coefficient, job satisfaction had 42,3% influence toward the performance of officers. Meanwhile, 57,7% was influenced by other variables. In conclusion, the study shows that job satisfaction had significant influence toward the performance of officers at the Directorate General of Sea Communication Navigation District Class 1 Dumai.Keywords: Job satisfaction, performance of officers